Zmiany w polityce i strategii marketingu stosowanej przez podmioty gospodarki żywnościowej - Kondratowicz-Pozorska, Jolanta (Changes in Politics and Marketing Strategy Used by Firms of Food Economy, 2006)
Competition is one of the basic mechanisms of free market. Nowadays a low price of products and its high quality is not enough to win the competition. There is necessity to have new ideas how to get new customers, keep the current ones and survive on the market. Active companies oriented on a customer are successful ones. Firms which change into this direction (being oriented on a customer) should enable a company to become a successful one. To get this effect there should be a change in standards of marketing strategies. The author presents changes which are made in understanding the 7P conception in food economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 447-454